Implementasi Manajemen Pembiayaan Pendidikan sebagai Peningkatan Mutu di TK Islam Bina Amanah Surabaya - Nur Afifah; Erni Munastiwi (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2022)
This study aims to explain the implementation of funding management, implementation of education funding management, and education funding management to improve the quality of education in Islamic Kindergarten Bina Amanah Surabaya. The method used in this research is observation, interviews, and documentation. The survey results show that 1) financing management planning is carried out by referring to the budget set by the government or the budget limit that does not exceed the budget set by parents or the community. If the funding comes from the government, then the need is from the rules set by the government. Funding revenues come from the city, and financial management plans are based on principles from primary school needs to tertiary needs, but within regulatory limits. 2) The steps for implementing madrasah funding include two main activities: school revenues and expenditures. Cash management activities include accounting or financial management activities. 3) Management/evaluation includes inspection and evaluation of the plan and implementation of the original financial plan and education funds that can be carried out in accordance with their implementation.